The West Kazakhstan legend kyuis (the problems of comparative stady of regional instrumental traditions) (Journal of Philosophy Culture and Political Science, 2018)
The articles puts forward a thesis on different musical styles of homonymous ancient legend kyuis in the East and the West of Kazakhstan. In the Western regions, the number of the legend kyuis is inconsiderable compared with the main kyuis (tokpe), which indicates that they were brought (from the East). Once on a new soil, these kyuis are influenced by local traditions and are built according to the canons of the main form of the region (bas – orta – saga). Analys of the kyuis «Aksak kulan» and «Nar idirgen» showed that the West Kazakhstan quint legend kyuis are essentially a combination of various musical structures, and in this case, a combination of ancient kyuis and tokpe: in significant development forms, it preserves quint structure and bourdon constitution. But this constitution has no overtone structure of OBP (overtone bourdon polyphony), as in the Eastern legend kyuis. The identified features of the musical style of the West Kazakhstan legend kyuis testify that these kyuis have preserved the essential elements of the ancient musical thinking and have the obvious signs of synthesis of the two musical systems (subsystems) – East Kazakhstan and West Kazakhstan. Key words: dombra tradition, legend kyuis, tokpe, shertpe, overtone structure, rhythm formula, musical intonation formula.